Effect of 12-O-tetradecanoylphorbol-13-acetate-induced psoriasis-like skin lesions on systemic inflammation and atherosclerosis in hypercholesterolaemic apolipoprotein E deficient mice. Issue 1 (December 2016) - Madsen, Marie; Hansen, Peter; Nielsen, Lars; Hartvigsen, Karsten; Pedersen, Anders; Christensen, Jan; Aarup, Annemarie; Pedersen, Tanja
Abstract Background Risk of cardiovascular disease is increased in patients with psoriasis, but molecular mechanisms linking the two conditions have not been clearly established. Lack of appropriate animal models has hampered generation of new knowledge in this area of research and we therefore sought to develop an animal model with combined atherosclerosis and psoriasis-like skin inflammation. Methods Topical 12-O -tetradecanoylphorbol-13-acetate (TPA) was applied to the ears twice per week for 8 weeks in atherosclerosis-prone apolipoprotein E deficient (ApoE−/− ) mice. Results TPA led to localized skin inflammation with increased epidermal thickness, infiltration of inflammatory-like cells and augmented tissue interleukin-17F levels. Systemic effects of the topical application of TPA were demonstrated by increased plasma concentration of serum amyloid A and splenic immune modulation, respectively. However, atherosclerotic plaque area and composition, and mRNA levels of several inflammatory genes in the aortic wall were not significantly affected by TPA-induced skin inflammation. Conclusions TPA-induced psoriasis-like skin inflammation in atherosclerosis-prone ApoE−/− mice evoked systemic immune-inflammatory effects, but did not affect atherogenesis. The results may question the role of psoriasis-induced inflammation in the pathogenesis of atherosclerosis in psoriasis patients.